A conserved interferon regulation factor 1 (IRF-1) from Pacific oyster Crassostrea gigas functioned as an activator of IFN pathway. Issue 76 (May 2018) - Lu, Mengmeng; Yang, Chuanyan; Li, Meijia; Yi, Qilin; Lu, Guangxia; Wu, Yichen; Qu, Chen; Wang, Lingling; Song, Linsheng
Abstract: Interferon regulatory factors (IRFs), a family of transcription factors with a novel helix-turn-helix DNA-binding motif, play important roles in regulating the expression of interferons (IFNs) and IFN-stimulated genes. In the present study, an interferon regulation factor 1 was identified from oyster Crassostrea gigas (designated Cg IRF-1), and its immune function was characterized to understand the regulatory mechanism of interferon system against viral infection in invertebrates. The open reading frame (ORF) of Cg IRF-1 was 990 bp, encoding a polypeptide of 329 amino acids with a typical IRF domain (also known as DNA-binding domain). The mRNA transcripts of Cg IRF-1 were detected in all the tested tissues with the highest expression level in hemocyte. Cg IRF-1 protein was distributed in both nucleus and cytoplasm of the oyster hemocyte. The mRNA expression of Cg IRF-1 in hemocytes was significantly up-regulated at 48 h after poly (I:C) stimulation ( p  < 0.05). The recombinant Cg IRF-1 (r Cg IRF-1) could interact with classically IFN-stimulated response elements (ISRE) in vitro . The relative luciferase activity of interferon-like protein promotor reporter gene (pGL- Cg IFNLP promotor) was significantly ( p  < 0.05) enhanced in HEK293T cell after transfection of Cg IRF-1. These results indicated that Cg IRF-1 could bind ISRE and regulate the expression of Cg IFNLP as a transcriptional regulatory factor, and participated in the antiviral immune response of oysters. Highlights: Cg IRF-1 is a conserved homologue of vertebrate IRF-1/2 family in oyster. Cg IRF-1 mRNA was highly expressed in oyster hemocytes, and was significantly up-regulated after poly (I:C) stimulation. Cg IRF-1 protein was localized in both nuclei and cytoplasm of oyster hemocytes. r Cg IRF-1 exhibited binding activities to classical ISRE in vitro. r Cg IRF-1 significantly activated the promotor of Cg IFNLP in HEK293T cells.